Relationship of Serum Calcium Level with Clinical Severity of Acute Ischemic Stroke as Assessed by National Institute of Health Stroke Score (NIHSS) - Saba Fatima, Fuad Shafiq, Yamna Fatima, Tahir Mahmood, Nafia Shahid, Maheen Maqsood (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Calcium (Ca2+) plays an important role in the pathogenesis of ischemic cell damage. Different studies have shown that lower serum calcium leads to more clinical severity of stroke as assessed by National Institute of Health Stroke Scale (NIHSS). Materials & Methods: Stroke patients who met the inclusion criteria were evaluated using NIHSS and their serum calcium levels were checked at presentation. Pearson’s correlation was determined between serum calcium levels and NIHSS score. Results: There were 200 patients in the study with mean age 61.58 ± 12.4 years. The male to female ratio was 1 : 1.15. The mean calcium level of the study population was 8.95 ± 0.75 mg/dL. The mean NIHSS score was 18.01 ± 7.91. The overall Pearson’s correlation coefficient between serum calcium level and NIHSS score came out to be r = - 0.413 (p < 0.001). The value was r = -0.396 (p = 0.29) among men and r = -0.416 among women (p = 0.12). Conclusion: Lower serum calcium levels is associated with more severe clinical findings at the onset of stroke. Keywords: Ischaemic stroke, Stroke severity, NIHSS score, Serum calcium